Respuesta :

Answer:

[tex]4x^5-5x^3-6x[/tex]

Step-by-step explanation:

Given: [tex](x^3-2x)(4x^2+3)[/tex]

To find: the product

Solution:

Use the property: Multiplication is distributive over addition that is [tex]a(b+c)=ab+ac[/tex]

[tex]\left ( x^3-2x \right )\left ( 4x^2+3 \right )=(x^3-2x)4x^2+(x^3-2x)3\\=4x^5-8x^3+3x^3-6x[/tex]

Add the like terms: [tex]-8x^3,3x^3[/tex]

(Like terms are terms that have same variables of same powers)

So,

[tex]\left ( x^3-2x \right )\left ( 4x^2+3 \right )=(x^3-2x)4x^2+(x^3-2x)3\\=4x^5-8x^3+3x^3-6x\\=4x^5-5x^3-6x[/tex]